2021
DOI: 10.3390/ijms222313093
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Role of ADAM17 in Renal Proximal Tubular Cells and Its Implications in an Obese Mouse Model of Pre-Diabetes

Abstract: Acute and chronic kidney lesions induce an increase in A Disintegrin And Metalloproteinase domain 17 (ADAM17) that cleaves several transmembrane proteins related to inflammatory and fibrotic pathways. Our group has demonstrated that renal ADAM17 is upregulated in diabetic mice and its inhibition decreases renal inflammation and fibrosis. The purpose of the present study was to analyze how Adam17 deletion in proximal tubules affects different renal structures in an obese mice model. Tubular Adam17 knockout male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Probably this mild protection against glucose intolerance can be explained by the modulation of Sodium-Glucose Cotransporter-2 (SGLT2) after Adam17 deletion. As we have recently described [ 31 ], Adam17 deletion may decrease SGLT2 activity, preventing HFD animals from proximal tubular glucose reabsorption by favouring its urinary excretion. HFD-mice with Adam17 deleted in endothelial cells presented decreased SGLT2 expression.…”
Section: Discussionmentioning
confidence: 81%
“…Probably this mild protection against glucose intolerance can be explained by the modulation of Sodium-Glucose Cotransporter-2 (SGLT2) after Adam17 deletion. As we have recently described [ 31 ], Adam17 deletion may decrease SGLT2 activity, preventing HFD animals from proximal tubular glucose reabsorption by favouring its urinary excretion. HFD-mice with Adam17 deleted in endothelial cells presented decreased SGLT2 expression.…”
Section: Discussionmentioning
confidence: 81%
“…The expression of ADAM17 in mouse articular cartilage is positively correlated with the development of arthritis, and its deletion attenuates articular cartilage degeneration (8). Moreover, ADAM17 is associated with glomerular inflammation and fibrosis (9). In diabetic mice, ADAM17 deletion in the proximal tubules improves glucose tolerance, prevents podocyte loss, and inhibits the accumulation of glomerular macrophages and collagen (9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ADAM17 is associated with glomerular inflammation and fibrosis (9). In diabetic mice, ADAM17 deletion in the proximal tubules improves glucose tolerance, prevents podocyte loss, and inhibits the accumulation of glomerular macrophages and collagen (9). More importantly, ADAM17 is contributory to the occurrence and development of cancers, including lung carcinoma (10), ovarian carcinoma (11), breast carcinoma (12)(13)(14), gastric carcinoma (15), and cervical carcinoma (16).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed a reduction in Gal3 and an improvement of beta-cell dysfunction (22). Study of renal function and prediabetic mouse model observed higher levels of Gal3 in the proximal tubules and glomeruli of HFD mice and attenuated by Adam17 depletion (45). Diabetic mouse model presented higher levels of Gal3 in liver and kidney and Gal3 was correlated with oxidative stress, specifically with AGE products and 3NT (22).…”
Section: Galectin-3 Animal Studies Clinical Studiesmentioning
confidence: 99%